Memahami Kesehatan & Keselamatan Kerja (K3) dan Implikasinya bagi Wisatawan - Semuel, Oktavianus W.; Loho, Ambrosius M.; Kerangan, Johanis; Sada, Fidy R. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The concept of Occupational Health & Safety (OHS) is important for a tourist trip, including tourists, tourism actors and owners of tourist destinations. The research outlines the concept of OHS, which is the main core of this writing. The purpose of this research is to outline the importance of occupational health and safety for tourists, so that their tourist trips can run well. On the same hand, this will be a determinant for a tourist trip. The method used in this research is descriptive analytical. This analytical descriptive method is pursued by describing the description of K3, then analyzed by using the hermeneutics of interpretation of the description. The results of data analysis found that an understanding of occupational health and safety is important that must first be known, not only by tourists but also by tourism actors and owners of tourist destinations